Table Tennis Footwork Skill Level of PJKR Students STKIP Darussalam Cilacap - Saefulah, Dian Imam; Aista, Syahida Cahya; Syifa, Ahmad (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
The problem in this research is the low achievement of PJKR STKIP Darussalam Cilacap students which is possibly caused by low footwork abilities. The aim of this research is to determine the footwork abilities of PJKR STKIP Darussalam Cilacap students. This type of research is descriptive where the researcher only wants to see the actual situation in the field regarding students' footwork abilities. PJKR STKIP Darussalam Cilacap. The population in this study was 34 PJKR STKIP Darussalam Cilacap students. The sampling technique used proportional random sampling, so the total sample was 11 people. To get data about the footwork of PJKR STKIP Darussalam Cilacap students, the test instrument is the table tennis footwork test. The analysis technique used is appropriate to the type of research, namely by using percentage calculations. Based on measurements and analysis, the following research results were obtained: The footwork ability of PJKR STKIP Darussalam Cilacap students is in the medium category with a percentage of 36.36%.